Are men getting more emotional? Critical sociological perspectives on men, masculinities and emotions - de Boise, Sam; Hearn, Jeff (The Sociological Review, 2017)
Sociological research, influenced by feminist and other critical perspectives, has noted how men’s emotional inexpressiveness was influenced, and supported, by patriarchal privilege. Such approaches have argued that ‘inexpression’ needs to be broken down in order to build gender equality and improve men’s own wellbeing. Emerging research has, however, challenged the argument that men are ‘emotionally inexpressive’ on two main premises: that, as a result of feminist critiques, many men now practise ‘softer’ or ‘more emotional’ forms of masculinity; second, that emotions always influence social action and so need to be better incorporated into sociological accounts of men’s behaviour. Yet these approaches entail some conceptual confusion as to what emotions are, how they link to social action and whether men’s emotions are inherently transformative for gender relations. This article first details how emotions and masculinity have been theorized in feminist-inspired approaches. It outlines recent work on emotions, men and masculinities before arguing for an understanding of emotions that engages with both physiologically grounded and postconstructionist debates. It finally suggests incorporating a material-discursive approach to men’s emotions, through feminist work on affect, which is attentive to the political dimensions of ‘increasing emotionality’ in order to contribute to a developing field of sociological research.
Keywords: approches et analyses; discipline; genre; inégalités; masculinité; privilèges; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; émotions

Revendiquer la transition de genre comme un travail : ce corps qui n’est pas le mien ? - Hanna, Lou (CONTRETEMPS, 2017)
Chercheuse indépendante en trans et queer studies, militante queer marxiste, dans cet article Lou Hanna tente d’établir un lien entre la transition de genre et le travail. En partant d’une analyse marxiste de l’expropriation de nos corps et de nos vies par le capitalisme néolibéral, il s’agit de tracer une continuité entre performance de genre et travail du genre. Cet article propose ainsi une conception des transidentités en rupture avec un discours hégémonique libéral qui tend à dépolitiser les acquis des luttes issus de l’activisme trans, de plus en plus axé sur une politique des droits au détriment d’une réelle politique révolutionnaire.
Keywords: approches et analyses; cours; discours dominant; europe; fem1300; france; genre; identités LGBTQIA2+; militance; personnes trans*; premier cycle; privilèges; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; violences

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité